Tackling the volatility paradox: Spillover persistence and systemic risk - Christian Kubitza (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
This paper proposes Spillover Persistence as a measure for financial fragility. The volatility paradox predicts that fragility builds up when volatility is low, which challenges existing measures. Spillover Persistence tackles this challenge by exploring a novel dimension of systemic risk: loss dynamics. I document that Spillover Persistence declines when fragility builds up, during the run-up phase of crises and asset price bubbles, and increases when systemic risk materializes. Variation in financial constraints connects Spillover Persistence to fragility. The results are consistent with the volatility paradox in recent macro-finance models, and highlight the usefulness of loss dynamics to disentangle fragility from amplification effects.
Keywords: E44; G01; G12; G20; G32; 330; Systemic Risk; Fragility; Financial Crises; Asset Price Bubbles; Fire Sales